1998
DOI: 10.1021/jp9724582
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on Unimolecular Reactions of Acetyl Cyanide and Acetyl Isocyanide

Abstract: The potential energy surfaces of acetyl cyanide and its functional isomer acetyl isocyanide in their electronic ground state have been investigated using ab initio molecular orbital MP2(FU)/6-311G** and QCISD(T)/6-311G** calculations. The molecular eliminations of CH3COX (X = CN,NC) to CH3X + CO, HX + CH2CO, and CH2 + HCOX, the unimolecular rearrangements to CH3C−OX and CH3O−CX carbenes, 1,3-hydrogen migration to CH2C(OH)X, 1,3-methyl migration to CH3NCCO, and radical decompositions to X• + CH3CO and CH3 • + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…The energy state of ts HCN is consistent with 273 kJ/mol predicted by Sumathi and Nguyen. 13 The ts HCN structure shows a H-CN distance of 1.821 Å, much larger than the bond length 1.066 Å in the HCN product. That is why, HCN is dissociated with vibrationally hot v 3 stretch mode.…”
Section: Photodissociation Mechanismmentioning
confidence: 91%
See 2 more Smart Citations
“…The energy state of ts HCN is consistent with 273 kJ/mol predicted by Sumathi and Nguyen. 13 The ts HCN structure shows a H-CN distance of 1.821 Å, much larger than the bond length 1.066 Å in the HCN product. That is why, HCN is dissociated with vibrationally hot v 3 stretch mode.…”
Section: Photodissociation Mechanismmentioning
confidence: 91%
“…38 Furthermore, the energy barriers to CH 3 and CN were calculated to be 369 (or 378) and 437 (or 484) kJ/mol by QCISD(T) (or MP2) method. 13 These two channels are kinetically less favorable at 308 nm.…”
Section: Photodissociation Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…In the theoretical investigation for the isomerisation of acetyl isocyanide to acetyl cyanide, Sumathi and Nguyen [14], and So [15] reported that the barriers of the isomerisation were 26.7 and 28.2 kcal mol À1 , respectively, and they concluded that the isomerisation was possible at low temperatures. In our theoretical study, P b2 0 isomerises to P b2 via TS18 with a barrier of 26.3 kcal mol À1 , and we infer that the interconversions between cyclopentadienyl isocyanides and cyclopentadienyl cyanides are feasible.…”
Section: The Interconversions Between Cyclopentadienylmentioning
confidence: 99%
“…The reactivities of ketene (CH 2 CO) and its derivatives have been widely studied [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Sumathi and Nguyen [14] and So [15] studied the unimolecular reaction of acetyl cyanide and acetyl isocyanide in theory, and revealed the potential energy profile of the decomposition reactions of acetyl isocyanide to CH 2 CO and HNC and acetyl cyanide to CH 2 CO and HCN.…”
Section: Introductionmentioning
confidence: 99%